Analysis of the Genesis Potential Index associated with Subtropical Cyclones near the Brazilian Coast - Ribeiro, João Gabriel Martins; da Paz, Gabriel Teodoro [UNESP]; Reboita, Michelle Simões [UNESP]; Gozzo, Luiz Felippe [UNESP] (Revista Brasileira de Geografia Fisica, 2023)
The coastal region of southern and southeastern Brazil, which is part of the South Atlantic Ocean basin, is a genesis region for subtropical cyclones and is, therefore, susceptible to weather change and impacts caused by these systems. The first named subtropical cyclone in the South Atlantic Ocean basin was Anita in 2010. Since then, several studies on subtropical cyclones have been carried out, but there are still several questions to investigate. Thus, this study aims to (a) describe the main physical mechanisms that caused the genesis of subtropical cyclones named in the South Atlantic Ocean between 2010 and 2021 and (b) identify the value of the Genesis Potential Index (GPI) between the pre-cyclogenesis and the phase in which these systems acquire subtropical characteristics. The reason for analyzing the GPI is to identify a possible pattern that helps in operational weather forecasting. The main database used in the study is the ERA5 reanalysis. Of the 14 cyclones studied, only two systems did not have genesis with subtropical characteristics, but acquired it 24 hours after cyclogenesis. There are 5 cyclones that showed genesis associated with mid-level troughs in the atmosphere, and 9 with blocking patterns (cutoff low type). As most of the studied cyclones occurred in an environment with a blocking structure, this indicates that the condition of weak vertical wind shear is an important factor for subtropical cyclones. Since the GPI does not show a standard value in the 14 cyclones studied, between pre-cyclogenesis and the moment when these systems become subtropical, as it varies from 0.35 in the Deni genesis to 22.71 in the Anita genesis, it may not be possible to use it with a threshold in operational practices.
Análise do Índice do Potencial de Gênese em Ciclones Subtropicais na Costa do Brasil
Keywords: coastal impacts; genesis potential index; subtropical cyclones; synoptic analysis